Method for producing composite for secondary battery electrode

The mechanochemical mixing of electrode active materials with fibrous carbon dispersion in a non-slurry form addresses the issues of high energy consumption and non-uniformity in existing methods, leading to improved conductivity and performance of secondary battery electrodes.

JP2025007168APending Publication Date: 2025-01-17TOYO INK MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023108390
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing methods for producing composite particles for secondary battery electrodes require high drying energy due to the use of solvents and struggle with uniform distribution of fibrous carbon, leading to non-uniform conductive networks and increased energy consumption.

Method used

A method involving mechanochemical mixing of electrode active materials with fibrous carbon dispersion in a non-slurry form, using a mechanochemical mixing device to disperse fibrous carbon uniformly on the active material surface, followed by solvent removal and drying, to achieve a homogeneous composite with high cohesive strength and conductivity.

Benefits of technology

This approach reduces drying energy consumption, ensures uniform fibrous carbon distribution, and enhances the conductivity of the electrodes, resulting in high-output, long-life nonaqueous electrolyte secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007168000001
    Figure 2025007168000001
  • Figure 2025007168000002
    Figure 2025007168000002
  • Figure 2025007168000003
    Figure 2025007168000003
Patent Text Reader

Abstract

To provide a composite for a secondary battery electrode having excellent electrical conductivity by precisely controlling the dispersion state of fibrous carbon on an active material.SOLUTION: A method for producing a composite for a secondary battery electrode containing an electrode active material and fibrous carbon includes a step of combining an electrode active material and a fibrous carbon dispersion in which the fibrous carbon is dispersed in a solvent in a non-slurry state by using a mechanochemical mixer, and a step of removing the solvent and drying the composite. The fibrous carbon dispersion is a dispersion containing carboxymethyl cellulose or a salt thereof and water, and the carboxymethyl cellulose or the salt thereof has a weight average molecular weight of 10,000 to 100,000 and a degree of etherification of 0.5 to 0.9.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a composite for a secondary battery electrode. [Background technology]

[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.

[0003] Furthermore, as the applications of lithium-ion secondary batteries expand, there is a demand not only for improved battery performance, such as higher capacity, faster charging, and longer life, but also for reduced battery costs and a reduced environmental impact in production. In particular, there is a growing need to reduce the environmental impact, which in turn leads to reduced CO2 emissions, and the reduction of energy consumption in the production of lithium-ion secondary batteries, which account for a large portion of the costs and energy consumed in the production of electric vehicles, has become an issue.

[0004] To address the above issues, a method of manufacturing electrodes by powder molding that does not require a composite slurry has been proposed, since a large amount of drying energy is required to remove the solvent in conventional electrode manufacturing methods that use a composite slurry. In electrode manufacturing by powder molding, issues include improving productivity and making the electrode material uniform, so composite particles of active materials are used, which are expected to improve the fluidity of the material and narrow the particle size distribution. For example, Patent Document 1 discloses a method for increasing thickness accuracy at low basis weight during powder molding by controlling the particle size distribution of composite particles produced by spraying and drying a slurry for composite particles containing an electrode active material, a water-soluble polymer, a binder resin, and a dispersion medium. Furthermore, Patent Document 2 discloses an example of producing composite particles with excellent particle strength by spray granulating a slurry containing a positive electrode active material, carbon black, and cellulose nanofibers. In addition, composite particles of active materials are expected to be used not only in powder molding but also in conventional manufacturing processes using composite slurries. In order to increase the capacity of secondary batteries, it is essential to increase the active material ratio in the electrode, so it is necessary to reduce the amount of auxiliary components. For this reason, the use of fibrous carbon, which has a small outer diameter and long fiber length and can form a conductive network with a small amount of addition, is seen as a promising conductive material. However, it is difficult to distribute it uniformly in the electrode because it conflicts with the large cohesive force. Therefore, a method has been proposed that uses composite particles with fibrous carbon adsorbed on the surface of the active material in advance. For example, Patent Document 3 discloses an example in which positive electrode active material particles and fibrous carbon are dispersed in a solvent using an ultrasonic disperser, and the resulting slurry is spray-granulated to produce composite particles in which the materials are uniformly mixed, and the composite particles are then made into an electrode after preparing a composite slurry. Furthermore, Patent Document 4 discloses an example in which a positive electrode active material and carbon nanotubes are combined in a nitrogen atmosphere by mechanochemical treatment to produce a positive electrode active material having high electronic conductivity and high mechanical strength. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6954424 [Patent Document 2] Patent No. 6380526 [Patent Document 3] Patent No. 5377946 [Patent Document 4] JP 2016-201228 A Summary of the Invention [Problem to be solved by the invention]

[0006] The methods disclosed in Patent Documents 1 to 3 require a spray granulation process when producing composite particles. A slurry in which the materials are uniformly dispersed is sprayed and instantly dried in a heating tank, making it possible to produce homogeneous composite particles. However, in order to spray the slurry in a spray form, it is necessary to reduce the viscosity of the slurry, and there is a limit to how much solid can be produced. Therefore, a larger amount of solvent is required than that used in conventional composite slurries, and the effect of reducing energy consumption in electrode production is not significant. In the method disclosed in Patent Document 4, composite particles can be produced without using a solvent because the carbon nanotubes are mixed in a powder state. However, it is difficult to disentangle the fibrous and entangled carbon nanotubes during the composite process, and the carbon nanotubes are not uniformly adsorbed onto the active material surface, resulting in non-uniform composite particles, making it difficult to form a uniform conductive network in the electrode.

[0007] The present invention aims to provide a method for producing composite particles that can solve the above-mentioned problems, i.e., reduce the drying energy required to remove the solvent during electrode production, while also achieving a uniform composite of highly cohesive fibrous carbon and active material, and to provide a composite for secondary battery electrodes that can achieve high conductivity even in the electrode. [Means for solving the problem]

[0008] The present invention relates to a method for producing a composite for a secondary battery electrode, comprising: A method for producing a composite for a secondary battery electrode, comprising the steps of: combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent, in a non-slurry state, by using a mechanochemical mixer; and removing the solvent and drying the resulting mixture, The fibrous carbon dispersion is a dispersion containing carboxymethyl cellulose or a salt thereof and water, The carboxymethyl cellulose or its salt has a weight average molecular weight of 10,000 to 100,000 and The degree of tellurization is 0.5 to 0.9, The present invention relates to a method for producing a composite for a secondary battery electrode, wherein the product (X×Y) of the complex elastic modulus X (Pa) and the phase angle Y (°) of the fibrous carbon dispersion is 100 or more and 1,700 or less.

[0009] The present invention also relates to the method for producing the composite for a secondary battery electrode, wherein the complex elastic modulus X is 50 Pa or less and the phase angle Y is 15° or more.

[0010] The present invention further relates to the method for producing a composite for a secondary battery electrode, wherein the fibrous carbon dispersion contains polyacrylic acid.

[0011] The present invention also relates to the method for producing the above-mentioned composite for secondary battery electrodes, characterized in that the exothermic peak temperature of the fibrous carbon obtained by simultaneous thermogravimetry-differential thermal analysis under an oxygen atmosphere is 520°C or less.

[0012] The present invention also relates to a method for producing the composite for a secondary battery electrode, wherein the complex elastic modulus X is 50 Pa or less and the phase angle Y is 15° or more.

[0013] The present invention also relates to a method for producing the composite for a secondary battery electrode, wherein the composite for a secondary battery electrode contains a binder resin.

[0014] The present invention also relates to a method for producing an electrode film formed by using the electrode composite for secondary batteries obtained by the above-mentioned method for producing an electrode composite for secondary batteries.

[0015] The present invention also relates to a method for producing a secondary battery including an electrode film obtained by the above-mentioned method for producing an electrode film. Effect of the Invention

[0016] According to an embodiment of the present invention, a composite for a secondary battery electrode having excellent electrical conductivity can be provided by precisely controlling the dispersion state of the fibrous carbon on the active material. According to still another embodiment of the present invention, a high-output, long-life non-aqueous electrolyte secondary battery and an electrode film used therein can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, a method for producing a composite for a secondary battery electrode according to an embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiment, and the present invention also includes embodiments that are implemented within the scope of the present invention.

[0018] In this specification, carbon nanotubes may be referred to as "CNTs." N-methyl-2-pyrrolidone may be referred to as "NMP." In this specification, a carbon nanotube dispersion may be simply referred to as a "CNT dispersion" or "dispersion." In addition, a composite for secondary battery electrodes may be referred to as an "electrode composite" or "composite."

[0019] <Method of manufacturing a composite for secondary battery electrode> The method for producing an electrode composite for a secondary battery of the present invention is characterized by including a step of combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer, and a step of removing the solvent and drying the resulting mixture.

[0020] In the process for producing the composite for secondary battery electrode of the present invention, the inclusion of the following (1) to (3) is an important factor for producing a composite having good resistance characteristics. (1) Uses a dispersion of fibrous carbon (2) Controlling the state of the mixture of the electrode active material and the dispersed carbon fiber (3) Compounding in a mechanochemical mixer The reasons for this will be explained below. (1) In order to adsorb fibrous carbon to the surface of an active material in the form of disintegrated primary particles or bundle particles, it is necessary to disintegrate the fibrous carbon, which has strong cohesive power, to the above-mentioned state, and dispersion in a liquid phase state (slurry) is essential for this. However, if it is combined with an active material in a slurry state, it is not possible to reduce the energy required to dry the solvent involved in electrode production. Therefore, it is necessary to use a dispersion of fibrous carbon in which the primary particles or bundle particles of fibrous carbon are uniformly dispersed and stabilized in advance. (2) By forming a composite in a non-slurry state with a high solid content concentration, it is possible to reduce the total amount of drying energy of the solvent in the electrode manufacturing using a conventional composite slurry. In addition, when the mixture is in a non-slurry state, it does not have fluidity as a liquid, so even if the composition has a smaller resin content than a general composite slurry, separation of components during drying and drying aggregation of fibrous carbon can be suppressed. The solid content concentration of the non-slurry mixture is preferably 60 mass% or more, and more preferably 80 mass% or more. The state of the mixture changes depending on the content of the solvent. In the order of the solvent content, it changes to a slurry state (with liquid fluidity), a clay-like state (without liquid fluidity, with viscosity), a crumbly state (without liquid fluidity, without viscosity), and a powder state (absolutely dry). In the present invention, the non-slurry state refers to a clay-like or crumbly state, but in order to suppress drying aggregation, mixing in a crumbly state is more preferable. (3) By mixing in a non-slurry state, it is expected that drying aggregation can be suppressed, but since it cannot flow as a liquid, the dispersion of fibrous carbon is difficult to wet and spread on the active material surface, and it is likely to become uneven. Therefore, by using a mechanochemical mixer capable of applying shear force to press the dispersion of fibrous carbon against the active material surface and promote wetting and spreading, it is expected that the fibrous carbon can be evenly adsorbed onto the active material surface while loosening the fibrous carbon. The above (1) to (3) make it possible to reduce the amount of drying energy required to prepare an electrode, to allow the fibrous carbon to be evenly adsorbed onto the surface of the active material in a loosened state, and to prevent separation of the components and aggregation of the fibrous carbon during drying during the process of concentrating and evaporating the solvent, thereby making it possible to obtain a composite and electrode with high electrical conductivity.

[0021] <Mechanochemical mixing device> The mechanochemical mixer is not particularly limited as long as it is a device capable of mixing a non-slurry mixture by applying a shear force. Examples of such machines include high-speed mixers such as the Henschel Mixer and Super Mixer, particle compounding devices "Nanocure", "Nobilta", and "Mechanofusion" manufactured by Hosokawa Micron Corporation, powder surface modification device "Miraro" manufactured by Nara Machinery Works, "Hivismix" and "Hivisdepermix" manufactured by Primix, mixers "Planetary Mixer" and "Trimix" manufactured by Inoue Manufacturing Co., Ltd., and mixer / granulator "High Speed ​​Mixer" manufactured by EarthTechnica Corporation. Among the mechanochemical mixers, planetary mixers, trimixes, and mechanofusions are preferred because they are capable of shear compounding and uniform mixing of materials.

[0022] <Electrode active material> The electrode active material is a material that causes a battery reaction required to extract electrical energy, and is not particularly limited. As the positive electrode active material, for example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides that can reversibly dope or intercalate lithium ions can be used. For example, lithium manganese composite oxides (e.g., Li x Mn 2 O 4 Or Li x MnO 2 ), lithium nickel composite oxide (e.g. Li x NiO 2 ), lithium cobalt oxide (Li x Chief of Staff 2 ), lithium nickel cobalt composite oxide (e.g. Li x Ni 1-y Co y O 2 ), lithium manganese cobalt composite oxide (e.g. Li x Mn y Co 1-y O 2 ), lithium nickel manganese cobalt composite oxide (e.g. Li x Ni y Co z Mn 1-y-z O 2 ), spinel-type lithium manganese nickel composite oxide (e.g. Li x Mn 2-yNi y O 4 ) and other composite oxide powders of lithium and transition metals, lithium phosphate oxide powders having an olivine structure (for example, Li x FePO 4 , Li x Fe 1-y Mn y PO 4 , Li x CoPO 4 etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxides (for example, V 2 O 5 , V 6 O 13 ), transition metal oxide powders such as titanium oxide, iron sulfate (Fe 2 (SO 4 ) 3 ), TiS 2 , and transition metal sulfide powders such as FeS. However, x, y, and z are numbers, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and 0 < y + z < 1. These cathode active materials can also be used alone or in combination of two or more. Among these active materials, in particular, active materials containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tend to have a high basicity due to components derived from raw materials or elution of metal ions, and due to this effect, gelation of the binder resin and deterioration of the dispersion state are likely to occur. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, the present embodiment is particularly effective.

[0023] As the negative electrode active material, for example, metal Li capable of reversibly doping or intercalating lithium ions, or its alloy, tin alloy, silicon-based material (such as metal Si, Si alloy, SiOx), LiXTiO2, LiXFe2O3, LiXFe3O4, LiXWO2 and other metal oxide systems, conductive polymers such as polyacetylene and poly-p-phenylene, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, resin-fired carbon materials can be used. However, x is a number and 0 < x < 1. These negative electrode active materials can be used alone or in combination of two or more. In particular, when using a silicon-based material, although the theoretical capacity is large, the volume expansion is extremely large, so it is preferably used in combination with artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, resin-fired carbon materials, etc.

[0024] <Fibrous carbon> Fibrous carbon is a fibrous carbon material, with a high aspect ratio in the super-axis direction, making it easier to form a conductive network compared to particulate carbon such as carbon black. Examples of fibrous carbon include carbon fiber (CNF) and carbon nanotube (CNT). Fibrous carbon has a shape in which planar graphite is wound into a cylindrical shape, including single-layer fibrous carbon, double-layer fibrous carbon, thin-layer (several layers) fibrous carbon, and multi-layer fibrous carbon, and these may be mixed. Single-layer fibrous carbon has a structure in which one layer of graphite is wound. Multi-layer fibrous carbon has a structure in which two or more layers of graphite are wound. Also, the side wall of the fibrous carbon does not have to be a graphite structure. Also, for example, fibrous carbon having a side wall with an amorphous structure is also fibrous carbon in this specification.

[0025] The shape of the fibrous carbon is not limited. Such shapes include various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stacking type), platelet-like (platelet), and coil-like. Among them, the shape of the fibrous carbon is preferably needle-like or cylindrical tube-like. The fibrous carbon may be of a single shape or a combination of two or more shapes.

[0026] Examples of the form of fibrous carbon include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. The carbon nanotubes may have a form consisting of a single one of these or a combination of two or more of these.

[0027] The average outer diameter of the fibrous carbon is preferably 100 nm or less, more preferably 50 nm or less. If the average outer diameter is too large, it may be difficult to uniformly combine with the composite. Also, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 13 nm or less. Also, it is preferably 1 nm or more, and more preferably 3 nm or more. The average outer diameter of the fibrous carbon can be calculated by observing and photographing the fibrous carbon with a transmission electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the outer diameter of each piece.

[0028] <Carboxymethylcellulose or its salt> Carboxymethylcellulose (CMC) or its salt is an anionic water-soluble polymer obtained from cellulose as a raw material. The CMC used in the present invention includes CMC having a weight-average molecular weight of 10,000 or more and 100,000 or less. In addition, 70,000 or less is more preferable, 60,000 or less is more preferable, and 30,000 or less is particularly preferable. By setting the weight-average molecular weight within the above range, the balance between the intermolecular force between the CMC and the fibrous carbon and the intermolecular force between the CMC and water is improved, and the CMC can be dispersed well and maintained in a good state. In addition, the degree of etherification of the CMC is 0.5 to 0.9, preferably 0.55 or more, more preferably 0.6 or more. In addition, 0.85 or less is preferable, and 0.8 or less is more preferable. By setting the degree of etherification within the above range, it is possible to provide an appropriate affinity for water and fibrous carbon. Furthermore, when used in a secondary battery, it is possible to prevent problems such as the dispersant dissolving in the electrolyte in the battery and increasing the viscosity of the electrolyte.

[0029] The method for producing CMC or its salt is not particularly limited, and it can be produced by a general method for producing CMC or its salt. That is, it is produced by carrying out a mercerization reaction in which an alkali is reacted with cellulose, and then adding an etherification agent to the obtained alkali cellulose to carry out an etherification reaction. For example, it can be produced by carrying out a mercerization reaction using a mixed solvent containing water and an organic solvent, adding monochloroacetic acid to carry out an etherification reaction, neutralizing the excess alkali with an acid, removing the mixed solvent, washing and drying, and then pulverizing. The molecular weight of the cellulose raw material can be reduced by extending the reaction time of the mercerization reaction.

[0030] The weight-average molecular weight of CMC is preferably 10,000 or more, more preferably 15,000 or more, in terms of pullulan. Also, it is preferably 100,000 or less, more preferably 60,000 or less, and even more preferably 30,000 or less. If it has a moderate weight-average molecular weight, the adsorption to the fibrous carbon is improved, and the stability of the dispersion is further improved. Also, if it is below the above range, the hygroscopicity is high and the film strength is likely to decrease. If it exceeds the above range, the viscosity increases due to hydrogen bonding in the aqueous solution, and the charging property and storage stability of the fibrous carbon decrease. Also, if it exceeds the above range, when a type of dispersing machine in which the dispersed liquid passes through a narrow flow path such as a nozzle-type high-pressure homogenizer is used, it becomes difficult to transfer the liquid to the narrow flow path, and the dispersion efficiency decreases.

[0031] Since many commercially available CMCs have a higher molecular weight than the above preferred range, they may be used after being hydrolyzed in an acidic aqueous solution to reduce their molecular weight. The weight-average molecular weight of the CMC to be hydrolyzed is preferably greater than 60,000 and less than 500,000. If the weight-average molecular weight exceeds 500,000, the hydrolysis reaction takes time and a large amount of oxidative decomposition products of CMC are generated, making purification difficult. The hydrolysis reaction in an acidic aqueous solution proceeds in a short time when heated and pressurized. The molecular weight of CMC can be controlled by adjusting the reaction time, temperature, and pH. The reaction can also be stopped by cooling and neutralizing with an alkali to a pH of 7 or higher. Acids and bases that are generally easy to obtain can be used.

[0032] The content of CMC or its salt is preferably 10% by mass or more, more preferably 20% by mass or more, based on the mass of the fibrous carbon. Also, it is preferably 100% by mass or less, more preferably 60% by mass or less, and even more preferably 40% by mass or less. By setting it within the above range, the fibrous carbon can be present well and stably without impairing the conductivity when used in a secondary battery electrode. Also, from the viewpoint of coating processability and storage stability, a CMC having a higher molecular weight than the CMC used in the dispersion may be added. When a high molecular weight CMC is added, it is preferable to add it after producing the fibrous carbon dispersion or at the end of the dispersion process. If it is added from the beginning of the dispersion, the viscosity of the dispersion medium becomes too high, which may cause problems such as a decrease in stirring efficiency, or a change in the adsorption equilibrium with respect to the fibrous carbon, which may cause a decrease in dispersibility.

[0033] <Solvent (dispersion medium)> The dispersion medium contains water and may contain, optionally, a water-soluble solvent, such as alcohols such as ethanol, propanol, butanol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether, and N-methyl-2-pyrrolidone (NMP).

[0034] <Carbon fiber dispersion> The fibrous carbon dispersion contains fibrous carbon and a dispersion medium, and optionally contains a dispersant. The fibrous carbon dispersion may contain optional components such as wetting agents, surfactants, pH adjusters, wetting penetrants, other additives such as leveling agents, other conductive materials, and other polymer components, as necessary, within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the dispersion, during dispersion, after dispersion, or a combination thereof.

[0035] The molecular weight of the polyacrylic acid used as the pH adjuster is not particularly limited, but the weight average molecular weight is preferably from 5,000 to 100,000, and more preferably from 10,000 to 50,000.

[0036] It is preferable to use polyacrylic acid as a pH adjuster that has not been neutralized. When the carboxyl group of polyacrylic acid is neutralized, a phenomenon called counterion condensation occurs, and the viscosity of the aqueous solution increases significantly. The increase in the aqueous solution viscosity not only deteriorates the handling properties of the fibrous carbon dispersion liquid, but also retains a small amount of moisture during the preparation of the electrode composition described below even after the drying process, which may affect the performance of the secondary battery.

[0037] The pH of the fibrous carbon dispersion is preferably 7.0 to 10.5, more preferably 9.0 to 10.5. If the pH is below the above range, the fibrous carbon dispersion is likely to gel. If the pH is above the above range, problems such as corrosion of various raw materials and exterior materials in the battery, or gelation of the binder are likely to occur. The pH can be measured by a general pH meter.

[0038] The dispersibility of fibrous carbon in the fibrous carbon dispersion can be evaluated by the complex modulus and phase angle measured by dynamic viscoelasticity measurement. The complex modulus indicates the hardness of the fibrous carbon dispersion, and the better the dispersibility of the fibrous carbon is and the lower the viscosity of the fibrous carbon dispersion is, the smaller the complex modulus becomes. However, when the fiber length of the fibrous carbon is large, even if the fibrous carbon is uniformly and stably dissolved in the medium, the complex modulus may be a high value because of the structural viscosity of the fibrous carbon itself. In addition, the phase angle means the phase shift of the stress wave when the strain applied to the fibrous carbon dispersion is a sine wave, that is, it indicates the ease of flow of the dispersion liquid. If it is a pure elastic body, it will be a sine wave in phase with the applied strain, so the phase angle will be 0°. On the other hand, if it is a pure viscous body, it will be a stress wave that has advanced by 90°. In a typical viscoelasticity measurement sample, the phase angle is a sine wave greater than 0° and less than 90°, and if the dispersion of the fibrous carbon in the fibrous carbon dispersion is good, the phase angle approaches 90°, which is the value of a pure viscous body. However, as with the complex modulus, if the fibrous carbon itself has structural viscosity, the phase angle may be a low value even if the fibrous carbon is uniformly and stably dissolved in the medium.

[0039] The complex modulus of the fibrous carbon dispersion is preferably 50 Pa or less, more preferably less than 20 Pa, more preferably 10 Pa or less, and even more preferably 5 Pa or less. The complex modulus of the fibrous carbon dispersion is preferably 0.01 Pa or more, more preferably 0.05 Pa or more, and even more preferably 0.1 Pa or more. The phase angle of the fibrous carbon dispersion is preferably 5° or more, more preferably 19° or more, even more preferably 30° or more, and particularly preferably 45° or more. The phase angle of the fibrous carbon dispersion is preferably 90° or less, more preferably 85° or less, and even more preferably 80° or less. The complex modulus and phase angle can be measured by the method described in the examples.

[0040] The complex modulus and phase angle of the fibrous carbon dispersion are determined by the dispersibility of the fibrous carbon in the fibrous carbon dispersion, the entanglement of the fibrous carbon, CMC, and other resin components, or the influence of their intermolecular forces, etc., so when the complex modulus X (Pa) and phase angle Y (°) are within the above preferred ranges and their product (X×Y) is 100 or more and 1,700 or less, a fibrous carbon dispersion with excellent dispersion stability can be obtained, and further, an excellent conductive network can be formed, thereby enabling the production of a composite and electrode film with extremely good conductivity. In addition, CMC with a weight average molecular weight of 10,000 to 100,000 and a degree of etherification of 0.5 to 0.9 has a small viscoelasticity by itself, but when it is made into a fibrous carbon dispersion, if the product (X×Y) of the complex modulus X (Pa) and the phase angle Y (°) is 100 to 1,700, it can play the role of a thickener or binder, and when it is made into a composite, the fibrous carbon on the active material surface is well dissolved and has excellent adsorption, and it is thought that the electrode strength and battery performance are improved. In addition, it is more preferable that the complex modulus is 50 Pa or less and the phase angle is 15° or more. It is not enough that the viscosity of the fibrous carbon dispersion is low and the (apparent) dispersibility is good, but it is particularly effective to judge the dispersion state by combining the complex modulus and the phase angle with conventional indicators such as viscosity.

[0041] The dispersibility of the fibrous carbon in the fibrous carbon dispersion can also be evaluated by the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer. With the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer, the particle diameter of the fibrous carbon aggregate particles can be estimated by the distribution of scattered light intensity by the particles. The median diameter (μm) is preferably 0.5 to 5.0, more preferably 0.5 to 2.0. By setting it within the above range, a fibrous carbon dispersion in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state will exist, and if it exceeds the above range, a large number of finely cut fibrous carbons will be generated, which may make it difficult to form an efficient conductive network. The median diameter can be measured by the method described in the examples.

[0042] The dispersibility of the fibrous carbon in the fibrous carbon dispersion can also be evaluated by measuring the gloss (i.e., the intensity of reflected light at an incident angle of 60°) of the coating film obtained by coating on a smooth glass substrate, baking and drying. For example, 1 mL of the fibrous carbon dispersion is dropped onto a smooth glass substrate, coated with a No. 7 bar coater at 2 cm / sec, baked in a hot air oven at 140°C for 10 minutes, and allowed to cool to obtain a coating film. Using a gloss meter (BYKGardner gloss meter microgross60°), three locations on the coating film surface, excluding the ends, are randomly selected, and the average value measured once can be used as the gloss at 60°. The better the dispersibility of the light incident on the coating film, the smoother the coating film surface becomes, and the higher the gloss. Conversely, the worse the dispersibility, the lower the gloss becomes, as light scattering occurs due to the unevenness of the coating film surface. The gloss at 60° can be measured by the method described in the examples. The gloss is preferably 5 or more, more preferably 50 or more, even more preferably 60 or more, and particularly preferably 70 or more. Also, it is preferably 120 or less, and even more preferably 110 or less. By setting it within the above range, a fibrous carbon dispersion in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state will exist, and if it is above the above range, a large amount of finely cut fibrous carbon will be generated, making it difficult to form an efficient conductive network.

[0043] The TI value of the fibrous carbon dispersion can be calculated by dividing the viscosity (mPa·s) at 60 rpm measured with a Brookfield viscometer by the viscosity (mPa·s) at 6 rpm. The TI value is preferably 2.0 or more and 5.0 or less. The higher the TI value, the greater the structural viscosity due to the entanglement of the fibrous carbon, CMC, and other resin components, or their intermolecular forces, and the lower the TI value, the smaller the structural viscosity. By setting the TI value within the above range, it is possible to suppress the entanglement of the fibrous carbon, CMC, and other resin components while allowing these intermolecular forces to act appropriately.

[0044] The fiber length of the fibrous carbon in the fibrous carbon dispersion of the present invention is preferably 0.3 to 5 μm, and more preferably 0.5 to 3.5 μm.

[0045] <Distribution method> The fibrous carbon dispersion of the present invention is preferably produced, for example, by dispersing fibrous carbon, CMC or its salt, and water using a dispersing device to finely disperse them. The dispersion treatment can be a multi-stage treatment of two or more steps by arbitrarily adjusting the addition timing of the materials to be used.

[0046] Examples of the dispersion device include a kneader, a two-roll mill, a three-roll mill, a planetary mixer, a ball mill, a horizontal sand mill, a vertical sand mill, an annular bead mill, an attritor, a high shear mixer, a high pressure homogenizer, and an ultrasonic homogenizer. In particular, from the viewpoint of promoting the wetting of the fibrous carbon and dissolving coarse particles, it is most preferable to use a high shear mixer in the initial dispersion step, and then to disperse the fibrous carbon while maintaining its fiber length. In addition, by dispersing the fibrous carbon with a high pressure homogenizer and then dispersing it with a bead mill, the dispersion state can be made uniform while maintaining the fiber length. The pressure when using the high pressure homogenizer is preferably 60 to 150 MPa, more preferably 60 to 120 MPa.

[0047] Dispersion methods using a dispersion device include batch dispersion, pass dispersion, circulation dispersion, etc., and any of these methods may be used, or two or more methods may be combined. Batch dispersion is a method in which dispersion is performed using only the dispersion device body without using piping or the like. It is easy to handle, so it is preferable for small-scale production. Pass dispersion is a dispersion method in which the dispersion device body is equipped with a tank that supplies the dispersion liquid through piping and a tank that receives the dispersion liquid, and the dispersion liquid is passed through the dispersion device body. In addition, circulation dispersion is a method in which the dispersion liquid that has passed through the dispersion device body is returned to the tank that supplies the dispersion liquid, and dispersion is performed while circulating. In either case, the longer the processing time, the more the dispersion progresses, so it is sufficient to repeat the pass or circulation until the desired dispersion state is reached, and the processing amount can be increased by changing the size of the tank or the processing time. Pass dispersion is preferable in that it is easier to uniformize the dispersion state compared to circulation dispersion. Circulation dispersion is preferable in that the work and manufacturing equipment are simple compared to pass dispersion. In the dispersion step, the disintegration of aggregated particles, the loosening, wetting, stabilization, etc. of the fibrous carbon proceed sequentially or simultaneously, and the final dispersion state differs depending on how the steps proceed, so it is preferable to control the dispersion state in each dispersion step by using various evaluation methods. For example, the dispersion state can be controlled by the method described in the Examples.

[0048] <Drying process> The method for removing the solvent and drying is not particularly limited as long as it can remove the solvent from the non-slurry mixture, and examples of the method include drying methods such as hot air drying, vacuum drying, freeze drying, etc. Among these, hot air drying and vacuum drying are preferred from the viewpoint of productivity.

[0049] <Composite for secondary battery electrodes> The composite for a secondary battery electrode contains an electrode active material, fibrous carbon, and may further contain an optional binder resin. The composite for an electrode may further contain optional components.

[0050] The fibrous carbon contained in the electrode composite of the present invention is at least partially crushed and adheres to the surface of the active material.

[0051] The presence of fibrous carbon in a crushed form on the surface of the active material can efficiently supply electrons required for the battery reaction to the active material, and can also contribute to reducing the contact resistance between active materials when an electrode is fabricated. Therefore, when the fibrous carbon is crushed and uniformly adsorbed on the surface of the active material to form an electrode for a secondary battery, the electrode resistance is reduced, and the formation of an electronic conduction path to the active material during the battery reaction is favored, thereby improving the battery rate characteristics and cycle characteristics. In addition, since an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, and the battery capacity can be improved.

[0052] The crushed form of fibrous carbon refers to a form in which secondary particles (aggregates) of fibrous carbon are broken down into primary particles or a bundle state in which multiple primary particles are bundled together. The state in which fibrous carbon is crushed and adsorbed onto the active material surface includes a state in which the primary particles and / or bundles are isolated, and a state in which the primary particles and / or bundles are overlapped. From the viewpoint of electron supply to the active material and conductive paths between composites, a state in which the primary particles and / or bundles are overlapped and adsorbed in a mesh-like shape is preferred.

[0053] In the present invention, the state in which the fibrous carbon is adsorbed on the surface of the active material in a crushed form means that the area of ​​the fibrous carbon adsorbed on the active material in a crushed fiber state is 10% or more of the entire surface of the active material, preferably 20% or more, and more preferably 50% or more.

[0054] The area occupied by the fibrous carbon adsorbed to the active material in the crushed fiber state can be measured from the contrast difference between the active material and the fibrous carbon in images taken at magnifications of 5,000 to 50,000 times using a scanning electron microscope (SEM) or a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), and the average value of the above areas calculated from 20 pieces of active material in the composite was used.

[0055] When the combustion temperature of the fibrous carbon in an oxygen-containing atmosphere is 550° C. or lower, the electrode composite of the present invention becomes a composite in a homogeneous state in which the fibrous carbon adsorbed on the active material surface is loosened.

[0056] The temperature of the exothermic peak in the present invention can be determined by TG-DTA (Thermogravimetry-Differential Thermal Analysis) measurement. Specifically, a TG curve and a DTA curve are obtained by performing TG-DTA measurement under air or oxygen flow conditions. In the obtained DTA curve, the top of the maximum exothermic peak resulting from the combustion of the fibrous carbon, which is located in the vicinity of 300 to 700°C, is read and determined as the temperature of the exothermic peak of the fibrous carbon. This represents the combustion temperature of the fibrous carbon. Generally, fibrous carbon has thick bundles in which primary particles are strongly aggregated by van der Waals forces, and large secondary aggregates in which bundles are aggregated together. The physical properties, such as thermal stability, differ depending on the state of aggregation. Therefore, even for the same type of fibrous carbon, the combustion temperature changes depending on the state of aggregation, and the stronger the aggregation, the higher the combustion temperature.

[0057] The combustion temperature of the fibrous carbon in the secondary battery electrode composite in an oxygen-containing atmosphere is preferably 520°C or less, since the fibrous carbon on the active material is adsorbed in a more loose state, which favors the formation of an electron conduction path from the fibrous carbon to the active material and improves the battery characteristics. It is preferably 480°C or less, and more preferably 450°C or less.

[0058] The secondary battery electrode composite is preferably in the form of particles, and the average particle size is preferably from 0.5 μm to 500 μm, more preferably from 1 μm to 200 μm.

[0059] As mentioned above, when the combustion temperature is 550°C or less and the volume resistivity is 100 Ω·cm or less, the fibrous carbon in the composite is crushed and is thin and uniformly adsorbed on the active material, which is preferable because when used as an electrode for a secondary battery, it reduces the electrode resistance and is favorable for the formation of an electronic conduction path to the active material during the battery reaction, improving the battery rate characteristics and cycle characteristics. In addition, because an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, making it possible to improve the battery capacity.

[0060] The content of fibrous carbon in the composite is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the composite for secondary battery electrodes. Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. If it exceeds the above range, the amount of active material filled in the electrode decreases, resulting in a decrease in battery capacity. In particular, for high-capacity batteries, 10% by mass or less is preferable. If it is below the above range, the conductivity of the electrode and battery may be insufficient.

[0061] The composite may contain a conductive material other than fibrous carbon. Examples of the other conductive material include carbon materials such as carbon black, fullerene, graphene, multilayer graphene, and graphite. The carbon black may be neutral, acidic, or basic, and may be oxidized carbon black or graphitized carbon black. The other conductive materials may be used alone or in combination of two or more.

[0062] <Binder resin> When the secondary battery electrode composition further contains a binder resin, there is no particular restriction as long as it is normally used as a binder resin for paints, and it can be appropriately selected according to the purpose. In addition, the binder resin used in the secondary battery electrode composition is a resin that can bond between substances such as active materials, CNTs, and other conductive materials, and in this specification, it may be a CMC that has a molecular weight, degree of etherification, etc. different from the CMC contained in the CNT dispersion of the present invention. Examples of the binder resin used in the secondary battery electrode composition include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as constituent units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, fluororesins; cellulose resins; elastomers such as styrene-butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins may also be used. Among these, when used as a binder resin for a positive electrode, polymers or copolymers having fluorine atoms in the molecule, such as polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene, are preferred from the viewpoint of structure. Furthermore, when used as a binder resin for the negative electrode, CMC with good adhesion (however, CMC with a different molecular weight, degree of etherification, etc. from the CMC contained in the CNT dispersion liquid of the present invention), styrene butadiene rubber, polyacrylic acid, etc. are preferred.

[0063] The content of the binder resin in the composite is preferably 0.1% by mass or more, and more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0064] <Electrode for secondary batteries> The secondary battery electrode of the present invention includes a composite for a secondary battery electrode. The electrode may further include optional components such as a binder and a dispersant. In general, the electrode is formed by powder compression molding or by applying a composite slurry onto a current collector and removing volatiles.

[0065] The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.

[0066] <Method of manufacturing secondary battery electrodes> A secondary battery electrode can be formed by adding a binder or the like to a composite for a secondary battery electrode, forming each component into a sheet by pressing or the like under dry conditions that do not contain solvents, and then powder pressure molding the sheet, or by preparing a composite slurry, coating it on a current collector, and removing the volatile components. The powder pressure molding method without using a composite slurry is preferable because it can reduce the energy consumption required for drying the solvent.

[0067] The method for powder compression molding is not particularly limited, and any known method can be used. When an electrode is produced by powder pressure molding without using a composite material slurry, a dry mixture in which the electrode composite and a binder are mixed in advance, or a dried product after wet mixing may be used. The method for adding a binder or the like to the secondary battery electrode composite and dry-mixing or wet-mixing each component is not particularly limited, and various dispersing machines, mixers, granulators, etc. can be appropriately selected.

[0068] When forming an electrode by adding a binder or the like to a composite for a secondary battery electrode by powder pressure molding and forming each component into a sheet by pressing or the like, each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be directly supplied to a current collector and pressure molded, or a free-standing film made of each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be prepared in advance and then laminated on a current collector. Also, a thin resin film serving as a binder component may be formed in advance on a current collector.

[0069] Examples of the method for powder pressure molding include a planographic press, a calendar roll, etc. Among them, the use of a calendar roll is preferred because of its productivity and ability to produce uniform molding.

[0070] The method for producing an electrode using the composite slurry is not particularly limited, and a known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.As a drying method after coating, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, and the like can be used, but are not particularly limited thereto.

[0071] After the composite slurry is applied, it may be rolled using a lithographic press, a calendar roll, etc. The thickness of the electrode film is, for example, 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0072] <Secondary battery> The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and at least one selected from the group consisting of the positive electrode and the negative electrode includes an electrode film made from the composite of the present invention.

[0073] The positive electrode may be an electrode film containing a positive electrode active material formed on a current collector, and the negative electrode may be an electrode film containing a negative electrode active material formed on a current collector.

[0074] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous solvent. As the electrolyte salt, various conventionally known electrolytes capable of moving ions can be used. For example, LiBF 4 , LiClO 4 , LiPF 6 , LiAsF 6 , LiSbF 6 , LiCF 3 SO 3 , Li(CF 3 SO 2 ) 2 N, LiC 4 F 9 SO 3 , Li(CF 3 SO 2 ) 3 C, LiI, LiBr, LiCl, LiAlCl, LiHF 2 , LiSCN, or LiBPh 4 (wherein Ph is a phenyl group), etc. The electrolyte salt is preferably dissolved in a non-aqueous solvent and used as an electrolyte solution.

[0075] The non-aqueous solvent is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0076] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.

[0077] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type.

[0078] The composite for secondary battery electrodes of the present invention is an ideal composite of active material and fibrous carbon, and therefore can be suitably used not only for electrodes made from composite slurries, but also for electrodes made by solid or semi-solid processes. Electrodes made by these solid processes can be applied not only to lithium ion secondary batteries using conventional electrolytes, but also to all-solid batteries and semi-solid batteries.

[0079] The secondary battery of the present invention can be suitably used as a battery for vehicles such as automobiles, and portable electronic devices such as personal computers and smartphones. EXAMPLES

[0080] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not exceed the gist of the invention. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". In addition, in the examples, "copolymer A" may be referred to as "copolymer" or "dispersant". In addition, in the examples, "dispersant-containing liquid" containing "dispersant" and a solvent may be referred to as "dispersant solution".

[0081] (Method of measuring weight average molecular weight (Mw)) The weight average molecular weight (Mw) of the produced carboxymethylcellulose sodium salt was measured by gel permeation chromatography (GPC) equipped with an RI detector under the following conditions. The molecular weight is a pullulan-equivalent value. Measurement sample: 0.1% by weight aqueous solution Equipment: HLC-8320GPC (Tosoh) Eluent: 0.1M NaCl aqueous solution Column: TSKgel SuperMultiporePW-M (Tosoh) Flow rate: 1.0mL / min Temperature: 25℃ Injection volume: 100μl

[0082] (Method for measuring degree of etherification) 0.6 g of sodium carboxymethylcellulose was dried at 105°C for 4 hours. The mass of the dried product was precisely weighed, then wrapped in filter paper and incinerated in a magnetic crucible. The incinerated product was transferred to a 500 ml beaker, and 250 ml of water and 35 ml of 0.05 mol / l aqueous sulfuric acid solution were added and boiled for 30 minutes. After cooling, the excess acid was back-titrated with a 0.1 mol / l aqueous potassium hydroxide solution. Phenolphthalein was used as an indicator. The degree of etherification was calculated from the measurement results using the following formula (1). (Degree of etherification) = 162 × A / (10000 - 80 A) (Equation 1) A = (af-bf1) / weight of dry matter (g) A: The amount (ml) of 0.05 mol / l sulfuric acid solution consumed by the combined alkali in 1 g of sample a: Amount of 0.05 mol / l sulfuric acid solution used (ml) f: Potency of 0.05 mol / l sulfuric acid solution b: Titration volume (ml) of 0.1 mol / l potassium hydroxide solution f1: Potency of 0.1 mol / l potassium hydroxide solution

[0083] (Preparation of Carboxymethylcellulose Sodium Salt) (Synthesis Example 1) 10 parts by mass of low-density pulp pulverized with a household mixer was charged into the tank of a planetary mixer (Hibis Dispermix 3D-2 type, manufactured by Primix). Then, 90 parts by mass of 15% by mass sodium hydroxide / IPA / aqueous solution (IPA:water mass ratio is 80:20) was charged into the tank and stirred at 40°C for 150 minutes to carry out a mercerization reaction, thereby obtaining an alkali cellulose. Next, 10 parts by mass of monochloroacetic acid was dissolved in 6 parts by mass of the above IPA / aqueous solution, and after adjusting to 25°C, the alkali cellulose was added over 60 minutes while maintaining the temperature at 35°C, and then the temperature was raised to 80°C over 30 minutes, and an etherification reaction was carried out at 80°C for 50 minutes. Then, the mixture was neutralized with 50% by mass of acetic acid to a pH of 7.0.

[0084] The solid component of the neutralized product was separated in a Buchner funnel, and then washed on the Buchner funnel by sprinkling a 70% by mass aqueous methanol solution to remove the by-products of sodium chloride, sodium glycolate, and sodium acetate. The product was transferred to a stainless steel square tray, dried in a hot air oven at 90°C for 4 hours, and pulverized to obtain carboxymethylcellulose sodium salt (CMC1). The weight average molecular weight and degree of etherification of the obtained carboxymethylcellulose sodium salt were as shown in Table 1.

[0085] (Preparation of Carboxymethylcellulose Sodium Salt) (Synthesis Examples 2 and 3) According to Table 1, CMCs 2 and 3 were obtained in the same manner as in Synthesis Example 1. The weight average molecular weight and degree of etherification of the obtained carboxymethylcellulose sodium salt were as shown in Table 1.

[0086] [Table 1]

[0087] (Method of measuring dispersed particle size) The particle size distribution was determined using a grind gauge with a maximum groove depth of 300 μm, according to a method conforming to JIS K5600-2-5.

[0088] (Method of measuring gloss) The sample for gloss measurement was prepared by dropping 1 mL of the fibrous carbon dispersion onto a smooth glass substrate, coating it with a No. 7 bar coater at 2 cm / sec, baking it in a hot air oven at 140°C for 10 minutes, and allowing it to cool. The coating area was approximately 10 cm x 10 cm. Using a gloss meter (BYK Gardner micro-gloss 60° gloss meter), three locations on the coating surface, excluding the edges, were randomly selected, and measurements were taken once each, with the average value being the gloss at 60°.

[0089] (Method for measuring viscosity of fibrous carbon dispersion) The viscosity of the fibrous carbon dispersion was measured using a B-type viscometer ("BL" manufactured by Toki Sangyo) at a dispersion temperature of 25°C. After thoroughly stirring the dispersion with a spatula, the viscosity was immediately measured at a rotor speed of 6 rpm and then at 60 rpm. The lower the viscosity, the better the dispersibility, and the higher the viscosity, the worse the dispersibility. Dispersions that clearly separated or settled were deemed to have poor dispersibility. The TI value was calculated by dividing the viscosity (mPa·s) at 60 rpm by the viscosity (mPa·s) at 6 rpm. A viscosity of less than 500 mPa·s for the fibrous carbon dispersion was considered excellent, 500 mPa·s to 2,000 mPa·s good, 2,000 mPa·s to 10,000 mPa·s poor, and 10,000 mPa·s or more was considered to have very poor sedimentation or separation.

[0090] (Measurement of complex modulus and phase angle of fibrous carbon dispersion) The complex modulus X and phase angle Y of the fibrous carbon dispersion were evaluated by performing dynamic viscoelasticity measurement at 25°C, a frequency of 1Hz, and a strain rate range of 0.01% to 5% using a rheometer (RheoStress1 rotational rheometer manufactured by ThermoFisherScientific Co., Ltd.) with a cone of 35mm diameter and 2°. The smaller the complex modulus obtained, the better the dispersibility, and the larger the complex modulus obtained, the worse the dispersibility. In addition, the larger the phase angle obtained, the better the dispersibility, and the smaller the phase angle obtained, the worse the dispersibility. Furthermore, the product (X×Y) of the obtained complex modulus X (Pa) and phase angle Y (°) was calculated. Complex modulus criteria ◎: Less than 10Pa (best) ○: 10 Pa or more but less than 20 Pa (excellent) △: 20 Pa or more but less than 50 Pa (good) △-: 50 Pa or more but less than 100 Pa (acceptable) ×: 100Pa or more (defective) Phase angle judgment criteria ◎: 45° or more (best) ○: 30° to less than 45° (Excellent) △: 15° or more and less than 30° (good) △-: 10° to 15° (OK) ×: Less than 10° (bad)

[0091] (Preparation of fibrous carbon dispersion) (Production Example 1) 93.7 parts by mass of ion-exchanged water was added to a stainless steel container, and 1.25 parts by mass of APP-84 (CMC) was added and dissolved while stirring with a disperser. Then, 2.0 parts by mass of BT1003 (fibrous carbon) was taken and added while stirring with a disperser. A square-hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed at a speed of 8,600 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less using a grind gauge. At this time, the dispersion particle size confirmed by the grind gauge was 180 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation type dispersion process was performed. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. After dispersing until the viscosity of the dispersion liquid measured at 60 rpm with a B-type viscometer (TOKISANGYO, VISCOMETER, MODEL:BL) was 3,000 mPa·s or less, 0.5 parts by mass of BT1003 was further added to the stainless steel container while stirring with a disperser, and a circulation dispersion process was again performed with a high-pressure homogenizer. After dispersing by circulation until the viscosity was 3,000 mPa·s or less with a high-pressure homogenizer, the work of adding BT1003 to the stainless steel container while stirring with a disperser was repeated a total of six times (the total amount of BT1003 added was 5.0 parts by mass). Subsequently, a 10-pass dispersion process was performed with the high-pressure homogenizer to obtain a fibrous carbon dispersion 1 containing 5.0 parts by mass of fibrous carbon.

[0092] (Examples 1 to 10) Fibrous carbon dispersions 1 to 10 were obtained in the same manner as in Production Example 1, except that the materials, compositional ratios, and number of pass-type dispersions shown in Table 2 were changed.

[0093] (Production Example 11) The fibrous carbon dispersion 3 obtained in Production Example 3 was placed in a stainless steel container, and 0.004 parts by mass of PAA was added while stirring with a disperser, to obtain a fibrous carbon dispersion 11 containing 5.0 parts by mass of fibrous carbon. The pH of the fibrous carbon dispersion 11 was 7.5.

[0094] (Production Example 12) Except for changing PAA to AC-10P, a fibrous carbon dispersion 12 was obtained in the same manner as in Production Example 11. The pH of the fibrous carbon dispersion 12 was 7.1.

[0095] (Production Example 13) Except for changing PAA to AC-10LP, a fibrous carbon dispersion 13 was obtained in the same manner as in Production Example 11. The pH of the fibrous carbon dispersion 13 was 7.0.

[0096] (Production Example 14) Except for changing PAA to HL415, a fibrous carbon dispersion 14 was obtained in the same manner as in Production Example 11. The pH of the fibrous carbon dispersion 14 was 7.5.

[0097] (Examples 15-17) 80 parts by mass of fibrous carbon dispersions 1 to 3 obtained in Production Examples 1 to 3 were placed in a glass bottle (M-140, manufactured by Kashiwa Glass Co., Ltd.), 140 parts by mass of zirconia beads (bead diameter 1.0 mmφ) were charged, and a dispersion treatment was performed for 2 hours using a Red Devil paint conditioner. After that, the zirconia beads were separated to obtain fibrous carbon dispersions 15 to 17.

[0098] (Example 18) 80 parts by mass of the fibrous carbon dispersion 3 obtained in Production Example 3 was placed in a glass bottle (M-140, manufactured by Kashiwa Glass Co., Ltd.), 0.012 parts by mass of MAC500LC and 140 parts by mass of zirconia beads (bead diameter 1.0 mmφ) were added, and a dispersion treatment was carried out for 5 hours using a Red Devil paint conditioner. After that, the zirconia beads were separated to obtain a fibrous carbon dispersion 18.

[0099] BT1003: LUCAN BT1003M (LG Chem Ltd., multi-walled CNT, fiber diameter 13 nm) ·8S:JENOTUBE8S (manufactured by JEIO, multilayer CNT, average outer diameter 6.8nm) APP-84: Sunrose APP-84 (Nippon Paper Industries, sodium carboxymethylcellulose) F01MC: Sunrose F01MC (Nippon Paper Industries, sodium carboxymethylcellulose) PAA: Polyacrylic acid (Wako Pure Chemical Industries, average molecular weight 25,000) AC-10P: Polyacrylic acid (Toa Synthetic, average molecular weight 9,000) AC-10LP: Polyacrylic acid (Toa Synthetic, average molecular weight 50,000) HL415: Polyacrylic acid (Nippon Shokubai, Aqualic, average molecular weight 10,000)

[0100] The weight average molecular weight and degree of etherification of the carboxymethyl cellulose or its salt used in the Production Examples were as shown in Table 1. The weight average molecular weight and degree of etherification were calculated by the same measuring methods as in the Production Examples.

[0101] [Table 2] [Table 3]

[0102] <Electrode composite for secondary batteries> (Example 1-1) According to the composition shown in Table 4, an electrode composite for a secondary battery was prepared as follows. First, fibrous carbon dispersion 1 was placed in a stainless steel container, and ion-exchanged water was added while stirring with a disperser, and the mixture was stirred for 10 minutes. Next, SiOx and the above dispersion were charged into a Trimix (TX-2L, manufactured by Inoue Seisakusho Co., Ltd.) container, and the mixture was stirred for 30 minutes at a rotation speed (revolution) of 50 rpm to prepare a mixture. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller. After that, the mixture obtained was taken out into a stainless steel vat and vacuum-dried at 100°C for 1 hour using a vacuum dryer to completely remove the solvent. The dried product was coarsely crushed in a mortar to obtain electrode composite for a secondary battery 1.

[0103] (Examples 1-2 to 1-18) According to the compositions shown in Table 4, Composites 2 to 18 were obtained in the same manner as in Example 1-1.

[0104] (Comparative Example 1-1) An electrode composite for secondary batteries was produced as follows according to the composition shown in Table 4. NMC and fibrous carbon were charged into a container of Mechanofusion (AMS-MINI, manufactured by Hosokawa Micron Corporation) and stirred at a rotation speed of 7000 rpm for 10 minutes to produce electrode composite for secondary batteries 19. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller.

[0105] (Comparative Example 1-2) According to the composition shown in Table 4, an electrode composite for a secondary battery was prepared as follows. First, the fibrous carbon dispersion 1 was placed in a stainless steel container, and ion-exchanged water was added while stirring with a disperser, and the mixture was stirred for 10 minutes. Next, SiOx and the above dispersion were charged into a Trimix (TX-2L, manufactured by Inoue Seisakusho Co., Ltd.) container, and the mixture was stirred for 30 minutes at a rotation speed (revolution) of 50 rpm to prepare a mixture. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller. After that, the mixture obtained was taken out into a stainless steel vat and vacuum-dried at 110°C for 3 hours using a vacuum dryer to completely remove the solvent. The dried product was coarsely crushed in a mortar to obtain an electrode composite for a secondary battery 20.

[0106] <Evaluation of the state of fibrous carbon in composites> The dispersion state of the fibrous carbon in the composite was determined using a JEOL JSM-7800F scanning electron microscope. · Criteria for determining aggregates of fibrous carbon ◎: Contains or does not contain fibrous carbon aggregates of 5 μm or less. ○: Contains aggregates of fibrous carbon larger than 5 μm and smaller than 10 μm. △: Contains aggregates of fibrous carbon larger than 10 μm and smaller than 50 μm ×: Contains aggregates of fibrous carbon larger than 50 μm Criteria for determining the surface disintegration state of fibrous carbon active material ◎: The area of ​​fibrous carbon adsorbed on the active material in a crushed fiber state is 50% or more of the entire surface area of ​​the active material. ○: The area of ​​the fibrous carbon adsorbed on the active material in a crushed state is 20% or more and less than 50% of the entire surface of the active material. △: The area of ​​the fibrous carbon adsorbed on the active material in a crushed state is 10% or more and less than 20% of the entire surface area of ​​the active material. ×: The fibers are not adsorbed to the active material in a crushed state.

[0107] <Exothermic peak temperature of fibrous carbon> The exothermic peak temperature of the fibrous carbon was evaluated using a differential thermobalance, ThermoplusEV02TG8121, manufactured by Rigaku Co., Ltd. The exothermic peak temperature obtained when the temperature was increased from 40°C to 800°C at 10°C / min while flowing compressed air at 200mL / min was used as an index. The exothermic peak temperature was calculated by reading the peak top temperature of the exothermic peak of the fibrous carbon in the range of 400 to 700°C on the DTA curve obtained by measurement.

[0108] [Table 4]

[0109] The abbreviations used in Table 4 have the following meanings: SiOx: (SILICONMONOOXIDE, SiOx 1.3C 5μm, manufactured by Osaka Titanium Technology Co., Ltd.)

[0110] As shown in Table 4, from the SEM and TG-DTA exothermic peak temperatures, it can be seen that in the Examples, the fibrous carbon in the composite was in a state of being moderately loosened and adsorbed on the active material surface without excessive aggregation. On the other hand, in the Comparative Examples, the breakup of the fibrous carbon agglomerates and the adsorption of the broken material on the active material surface were insufficient.

[0111] <Preparation of negative electrode film> (Example 2-1) The composite electrode prepared in the example was used to prepare a negative electrode film. Three parts of styrene butadiene rubber as a binder, 92.1 parts of natural graphite CGB-20, and 4.9 parts of electrode composite 1 were weighed out and placed in a plastic container, and stirred for 15 seconds at 2,000 rpm using a centrifugal mixer (Thinky's Awatori Rentaro, ARE-310). The resulting powder mixture was calendered onto a 20 μm-thick copper foil current collector using a powder feeder and calender roll (roll temperature 120°C), to obtain an electrode film for the negative electrode 20. The density of the electrode film for the negative electrode was 1.5 g / cm. 3 It was.

[0112] (Examples 2-2 to 2-18, Comparative Examples 2-1 and 2-2) Negative electrode films 2 to 20 were obtained in the same manner as for the negative electrode film 1 using the composites 2 to 20.

[0113] <Assembly of a cell for evaluating the negative electrode of a lithium-ion secondary battery> The previously prepared electrode films 1 to 20 were punched out to φ16 mm to be used as working electrodes, and metallic lithium foil (thickness 0.15 mm) was used as a counter electrode. A separator (porous polypropylene film) was inserted between the working electrode and the counter electrode and laminated. An electrolyte (a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a ratio of 3:5:2 (volume ratio) was prepared, and VC (vinylene carbonate) and FEC (fluoroethylene carbonate) were added as additives at 1 part by mass each to 100 parts by mass of the mixed solvent, and then LiPF 6 A two-electrode sealed metal cell (Hosen HS Flat Cell) was assembled by filling it with a non-aqueous electrolyte solution in which 1M of 1M was dissolved in water. The assembly of the cell was carried out in a glove box purged with argon gas.

[0114] <Evaluation of rate characteristics of negative electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery negative electrode evaluation cell thus prepared was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C and a charge end voltage of 0.05V, constant current discharging was performed at a discharge rate of 0.2C and a discharge end voltage of 1.5V. After repeating this operation three times, constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C and a charge end voltage of 0.05V, and constant current discharging was performed at a discharge rate of 3C and a discharge end voltage of 1.5V. 1C was the current value at which the theoretical capacity of the negative electrode was charged or discharged in 1 hour. The rate characteristic can be expressed by the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 2. (Formula 2) Rate characteristic = 3C discharge capacity / 3rd 0.2C discharge capacity × 100 (%) A relative value (%) was calculated based on the rate characteristic of Comparative Example 2-2, and evaluated according to the following criteria. ◎: 150% or more (very good) ○: 100% or more but less than 150% (Excellent) ×: Less than 100% (defective)

[0115] <Evaluation of cycle characteristics of negative electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery negative electrode evaluation cell thus prepared was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C with a charge end voltage of 0.05V, constant current discharging was performed at a discharge rate of 0.2C with a discharge end voltage of 1.5V. This operation was repeated 10 times. 1C was the current value at which the theoretical capacity of the negative electrode was charged or discharged in 1 hour. The cycle characteristics can be expressed as the ratio of the 3rd 0.2C discharge capacity to the 10th 0.2C discharge capacity, as shown in the following formula 1. (Formula 1) Cycle characteristic = 3rd 0.2C discharge capacity / 10th 0.2C discharge capacity × 100 (%) The relative value (%) was calculated based on the cycle characteristic of Comparative Example 2-2, and was evaluated according to the following criteria. ◎: 150% or more (very good) ○: 100% or more but less than 150% (Excellent) ×: Less than 100% (defective) [Table 5]

[0116] As shown in Table 5, the examples showed superior battery characteristics compared to the comparative examples. The fibrous carbon in the composite of the examples was loosened and adsorbed on the surface of the active material without excessive aggregation. Therefore, it is presumed that the conductive path in the electrode can be uniformly formed, leading to a reduction in electrode resistance and an improvement in rate characteristics and cycle characteristics. Among them, those in which the fibrous carbon was well adsorbed showed particularly good performance. On the other hand, in the comparative example, insufficient crushing of the fibrous carbon during the composite manufacturing process and excessive drying and aggregation during the drying process resulted in a decrease in the amount of adsorption onto the active material surface and uneven distribution of the material, which is presumably responsible for the uneven formation of conductive paths within the electrode, leading to an increase in electrode resistance and deterioration of rate characteristics and cycle characteristics. From the above, it was demonstrated that the electrode composite produced by the production method of the present invention can exhibit excellent battery characteristics.

Claims

1. A method for producing a composite for a secondary battery electrode, comprising: A method for producing a composite for a secondary battery electrode, comprising the steps of: combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent, in a non-slurry state, by using a mechanochemical mixer; and removing the solvent and drying the resulting mixture, The fibrous carbon dispersion is a dispersion containing carboxymethyl cellulose or a salt thereof and water, The carboxymethyl cellulose or its salt has a weight average molecular weight of 10,000 to 100,000 and The degree of tellurization is 0.5 to 0.9, A method for producing a composite for a secondary battery electrode, wherein the product (X×Y) of the complex elastic modulus X (Pa) and the phase angle Y (°) of the fibrous carbon dispersion is 100 or more and 1,700 or less.

2. 2. The method for producing a composite for a secondary battery electrode in accordance with claim 1, wherein the complex elastic modulus X is 50 Pa or less and the phase angle Y is 15° or more.

3. The method for producing a composite for a secondary battery electrode according to claim 1 or 2, wherein the fibrous carbon dispersion further contains polyacrylic acid.

4. 3. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the fibrous carbon has an exothermic peak temperature of 520° C. or less, as determined by simultaneous thermogravimetry and differential thermal analysis in an oxygen atmosphere.

5. 3. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the composite for a secondary battery electrode contains a binder resin.

6. A method for producing an electrode film formed by using the electrode composite for secondary batteries obtained by the method for producing an electrode composite for secondary batteries according to claim 1 or 2.

7. A method for producing a secondary battery comprising an electrode film obtained by the method for producing an electrode film according to claim 6.

Citation Information

Patent Citations

  • Hydraulic clutch switch valve

    JP1978077946A

  • Optical processing apparatus

    JP1988080526A

  • Active material and battery using the same

    JP2016201228A

  • Composite particles for electrochemical element electrodes, electrochemical element electrodes, and electrochemical elements

    JP6954424B2